STEAM Fair: Proyek Program Pendidikan Pembangunan Berkelanjutan di Sekolah Dasar Chalidana Islamic School Menganti - Lailashafra, Arum; Nugraheni, Nursiwi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article discusses a sustainable education program project that has been implemented by a private school in the Gresik area. Through the annual STEAMÂ  Fair, Chalidana Islamic School Primary Menganti instills sustainable education creatively and meaningfully for its students. This study is conducted using a qualitative descriptive approach, through methods such as interviews with the Person in Charge (PIC), analysis of written project planning, and documentation review. The aim of this article is to explore the best practices and experiences from the implementation of sustainable education programs in elementary schools and provide valuable insights for other schools interested in adopting a similar approach to enhance sustainable learning.